Recycled aggregates from construction and demolition waste towards an application on structural concrete: A review - de Andrade Salgado, Fernanda; de Andrade Silva, Flávio (Journal of Building Engineering, 2022)
The construction sector, in addition to being very important for the economy of several countries, also has a significant impact on the environment as it causes a huge natural resources depletion and generates an enormous amount of waste. Therefore, the use of recycled aggregate from construction and demolition waste, instead of conventional aggregates, has a double environmental advantage: it decreases the consumption of natural resources and reduces the land needed for waste disposal. Thus, in the last decades, many researches have been conducted to analyse the feasibility of recycled aggregate in several civil engineering works, which can help in a long way the economic and environmental sustainability of countries. This article presents a literature review on the production and utilization of recycled aggregate in concrete. Because of its higher water absorption and lower density, the use of recycled aggregate can cause a slight reduction in workability and compressive strength of concrete. Thus, authors have evaluated methods to remove the adhered mortar or to seal the pores of recycled aggregates, enhancing the material quality. Some articles also show the feasibility of using recycled aggregate concrete in structural elements, either through reduced-scale elements at a laboratory or full-scale elements in real projects. Summarily, this review may help to alleviate the concerns of consumers and further promote the use of recycled aggregate on a larger scale in civil engineering. The literature survey was conducted on an extensive database; however, a greater emphasis was placed on articles published after the year 2000. •Recycled aggregate is a sustainable solution for environmental depletion of construction sector.•Properties of recycled aggregates can be improved by different methods.•Standards usually limit the use of recycled aggregate to 30% in structural elements.•There is no consensus on methods of mix design for recycled aggregate concrete.•It is important to develop technical specifications for structural recycled aggregate concrete.